Multilingualism and language attitudes: Students perceptions towards kiswahili in Mtwara Region of Tanzania - Wamalwa, Eric W.; Adika, Stanley K.; Kevogo, Alex U.; Mtwara, Stella Maris (Research on Humanities and Social Sciences, 2013)
The role of language attitudes on language choice, development and policy in multilingual societies cannot be over emphasized (Adegbija, 1994; Batibo, 2005). Monolingual speakers have only one attitude towards their language because they have no other languages to compare it with. However, where speakers are bilingual or multilingual; there is a tendency to develop different attitudes to each of the languages used. These attitudes, whether positive or negative, will normally depend on the degree of symbolic or socio-economic value manifested by each language. Tanzania, a multilingual country with over 128 languages and with a bilingual language policy in education is therefore a fertile ground for studies on language attitudes. In recent years, there have been concerted efforts by various stake holders to propagate growth and development of English in Tanzania. English has been lauded as the essential language which links Tanzania to the rest of the world through technology, commerce and administration. Against this backdrop, this study sought to investigate students’ attitudes towards Kiswahili so as to determine whether the shift to English had impacted students’ attitude formation towards Kiswahili. This survey comprised of 340 students sampled from six selected schools of Mtwara Urban and Mtwara Rural districts. Results show that most Tanzanian students have favourable attitudes towards Kiswahili and the language’s status among secondary school students has not diminished. Kiswahili remains the most preferred language of use in all major domains. This study proposes that the place and role of Kiswahili be further enhanced in the country by exploring its possible use as a medium of instruction at secondary school level. Further, the study proposes that local vernaculars, which face extinction due to language shift that has taken place, need drastic measures in order to preserve them.
Keywords: Multilingualism; Bilingual education; language attitudes; Kiswahili